Systematic review of published studies on aquatic exercise for balance in patients with multiple sclerosis, Parkinson's disease, and hemiplegia - Pichanan Methajarunon, MSc, PT; Chachris Eitivipart, MSc, PT; Claire J. Diver, PhD, Grad Dip Phys, MCSP, PG Cert Res; Anchalee Foongchomcheay, PhD, PT (World Scientific Publishing, 2016)
Background: Multiple sclerosis, Parkinson's disease, and hemiplegia are common disorders that directly cause impairment of balance and gait. Aquatic exercises are used for neurological rehabilitation. It is suggested that the contributing factors of the water setting such as buoyancy, viscosity, and hydrostatic pressure offer an ideal environment for rehabilitative programmes. Objective: To conduct a systematic review of studies that assess the effect of aquatic exercises on balance in neurological patients (i.e., patients with multiple sclerosis, Parkinson's disease, and hemiplegia). Methods: A systematic literature search of six databases (MEDLINE, PEDro, AMED, CINAHL, Embase, SPORTDiscus) for randomized controlled trials and quasi-experimental trials on aquatic exercises in three different neurological disorders, namely, multiple sclerosis, Parkinson's disease, and hemiplegia, was performed. Reference lists from identified studies were manually searched for additional studies. Methodological quality was assessed using the Downs and Black checklist. The data were analyzed and synthesized by two independent reviewers. Disagreements in extracted data were resolved by discussion among the reviewers. Results: The methodological quality of eight studies included in this review ranged from fair to good. The findings illustrated that there were statistically significant improvements in static and dynamic balance in patients with multiple sclerosis and hemiplegia. The statistically significant improvements in gait ability were only found in the studies conducted on multiple sclerosis. No conclusions can be drawn in Parkinson's populations as only two trials conducted with a small sample size were available. Conclusion: Aquatic exercises may be effective at improving balance impairment in patients with hemiplegia and multiple sclerosis. There is a need for further research investigating its effect on Parkinson's disease before encouraging the use of aquatic exercises.